Investigations’ ethical aspects regarding pharmaceutical products’ biodisponibility and bioequivalence in Latin American legislations - Moreno Exebio, Luis (Acta Bioethica, 2004)
This paper pretends to identify the ethical criteria established in certain countries with up-to-date norms on biodisponibility/bioequivalence, and to determine if such criteria really protect participants in these investigations. In order to obtain information a questionnaire on biodisponibility/bioequivalence topics was sent via e-mail to the medicaments’ regulating agencies in Argentina, Bolivia, Brasil, Chile, Colombia, Costa Rica, Ecuador, México, Paraguay, Perú, Uruguay and Venezuela. Conclusions show that up-to-date norms regarding necessary ethical aspects to protect people who participate in those investigations are unequal Ethical requirements should be uniformed so as to allow a quicker legislation development in those countries that still lack it. This would also strengthen the region’s pharmacaeutical regulations